2013
DOI: 10.1089/lap.2012.0485
|View full text |Cite
|
Sign up to set email alerts
|

A Clinical Comparison of Laparoscopic Nissen and Toupet Fundoplication for Gastroesophageal Reflux Disease

Abstract: In the short term, the incidence of dysphagia was significantly lower after Toupet fundoplication, but the difference decreased significantly with extension of the postoperative recovery period. For patients with moderate to severe GERD, the laparoscopic Nissen fundoplication may be optimal; for elderly patients or for patients with significantly reduced esophageal peristalsis detected in preoperative examinations, the laparoscopic Toupet fundoplication should be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 18 publications
1
39
0
Order By: Relevance
“…Finally, the literature search identified 13 RCTs [ 6 , 7 , 12 , 15 17 , 19 , 20 25 ] published between June 1997 and July 2013. A total of 814 (52.05%) patients underwent LNF and 750 (47.95%) patients underwent LTF.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Finally, the literature search identified 13 RCTs [ 6 , 7 , 12 , 15 17 , 19 , 20 25 ] published between June 1997 and July 2013. A total of 814 (52.05%) patients underwent LNF and 750 (47.95%) patients underwent LTF.…”
Section: Resultsmentioning
confidence: 99%
“…Seven trials [ 6 , 12 , 15 , 17 , 19 , 21 , 25 ] reported mean operative time ( S2 Fig ), which ranged from 35.5 [ 15 ] to 155 [ 19 ] min in the LNF group and 32.5 [ 15 ] to 162 [ 19 ] min in the LTF group. Operative duration was shorter in the LNF group, but no significant difference was found between groups (LNF vs. LTF, standard mean difference -0.45, 95% CI [-1.00, 0.11], p = 0.11).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Many articles comparing the outcomes of laparoscopic Nissen and Toupet fundoplication have been published [20][21][22][23][24]. In the current study, in terms of indications for redo-ARS, the most common cause of failure of the prior ARS was dislocation of the wrap and recurrence of the hiatal hernia.…”
Section: Discussionmentioning
confidence: 71%